Nephrin expression in human epidermal keratinocytes and its implication in poor wound closure. Issue 7 (23rd June 2022) - Kim, Ji Young; Lee, Eun Jung; Seo, Jimyung; Lee, Yangsin; Ahn, Yuri; Park, Sujin; Bae, Yu Jeong; Lee, Jinu; Lim, Beom Jin; Kim, Doyoung; Cho, Jin Won; Oh, Sang Ho
Abstract: Nephrin is a type‐1 transmembrane protein and a component of the slit diaphragm renal‐filtration barrier. It has several functions in actin remodeling and cell–cell adhesion. Nephrin is principally located in the kidney glomerulus, but several studies have reported that nephrin is found in the pancreas, brain, and placenta. However, nephrin expression and its role in human skin have not yet been reported. First, using single‐cell RNA sequencing, immunohistochemistry, and immuno‐electron microscopy, nephrin expression was confirmed in human‐skin epidermal keratinocytes. Nephrin expression colocalized with the expression of zonula occludens‐1 in keratinocytes and was closely related to keratinocyte cell density, proliferation, and migration. High glucose treatment decreased nephrin expression and compromised keratinocyte cell migration without yes‐associated protein nuclear entry. This reduced cell migration under high glucose conditions was improved in nephrin‐overexpressing keratinocytes. Nephrin was highly expressed on the margins of re‐epithelized epidermis based on in vivo mice and ex vivo human skin wound models. The results demonstrate that nephrin is expressed in human‐skin keratinocytes and functions in cell adhesion, proliferation, and migration. In conclusion, this study suggests that nephrin may have a variety of physiological roles in human skin.